Navigating and Creating (Canadian Review of Art Education / Revue canadienne d'éducation artistique, 2022)
During the various stages of the Covid 19 pandemic, artistic practices have become increasingly important in managing the complexity of the impacts of the pandemic (Sabol, 2022). From simple rainbow drawings to musicians performing from their balconies, creating art has been essential to navigating these unprecedented times as we encounter our lives through different lenses due to new and shifting realities. In 2021, Dr. Julie Ethridge, Vice President of the CSEA/SCÉA invited artists of all artistic backgrounds to submit work that was shaped and created during the first 12 months of the global pandemic that addressed how (if) the pandemic intersected with their artistic practice. The works that were included in the virtual exhibit that ran from July to October 2021 are shown here, with the artist’s statements.